A first case of successful using of ibrutinib in treating paraneoplastic pemphigus related bronchiolitis obliterans concurrent with CLL - Chen, Can; Xu, Ying; Yu, Jingdi; Qian, Shenxian; Xie, Yaping (Frontiers in Medicine, 2023)
Paraneoplastic pemphigus (PNP) is a rare life-threatening disease which always associated with an underlying neoplasm. Tumor-related PNP most commonly precedes the detection of a hematological malignancy, with some cases seen during disease remission following cytotoxic drug therapy or radiotherapy. The lung is the most frequently-involved site in PNP, second only to the eyes, and involvement is seen in 59.2% to 92.8% of PNP cases. Bronchiolitis obliterans (BO) is the end stage of respiratory involvement and is regarded as life-threatening. The key point in treatment of PNP is to control the associated underlying hematologic neoplasia. High-dose systemic corticosteroids combined with other immunosuppressants are considered the first line of treatment. Other therapies that have shown beneficial effects include plasmapheresis, intravenous immunogloblin (IVIG), and more recently, daclizumab, alemtuzumab, and rituximab. There is no effective treatment for BO with PNP, and suppression of the cellular immune response may be necessary. Patients with PNP-BO associated with lymphoma mostly die within approximately 1 year. Herein, we reported a patient who diagnosed with PNP-BO concurrent with chronic lymphocytic leukemia. He was successful treated with ibrutinib and had achieved the longest survival which suggested that ibrutinib may be the best treatment choice for such patient.